Mapping Research Trends in Translanguaging in English Language Teaching: A Scopus-Based Bibliometric Analysis - Belly Ubaidila; Rizka Safriyani (Edulitics (Education, Literature, and Linguistics) Journal, 2026)
This study employed bibliometric analysis to present trends in the development of translanguaging research in English Language Teaching (ELT) on the Scopus database from 2014 to 2026. The study aims to systematically map annual scientific production, most productive authors, most productive sources, most relevant affiliations, most cited countries, keyword co-occurrence networks, and thematic maps. A descriptive quantitative method was used, with a final dataset of 437 Scopus-indexed journal articles from 2014 to 2026 (partial records), using the keyword "translanguaging" and “English Language Teaching”, then using the R-Bibliometrix Package (Biblioshiny R) to analyze and map out the data. The inclusion criteria and search strategy were carefully applied to ensure a relevant analysis. The results reveal a substantial growth in translanguaging studies publications, starting low at 1 per year from 2014-2015 and peaking at 115 in 2025. Fang F is the most productive author with 7 documents throughout the year. The top sources are the International Journal of Bilingual Education and Bilingualism and the International Journal of Multilingualism, with each contributing 18 documents. The University of the Basque Country leads affiliations with 11 publications, and the United States (USA) has the highest citations (1,201). The co-occurrence network analysis shows the relationship between different research topics, such as bilingual education, multilingualism, and English medium instruction (EMI). The thematic map identifies motor themes like English as a second language, basic themes like multilingualism, niche themes like languaging, and emerging themes like EAP. By understanding these trends, educators, researchers, and policymakers can better promote and explore translanguaging practices to support the effective ELT process in multilingual contexts.